2015
DOI: 10.1016/j.susc.2014.09.017
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of organic molecules at the TiO2(110) surface: The effect of van der Waals interactions

Abstract: Abstract. Understanding the interaction of organic molecules with TiO 2 surfaces is important for a wide range of technological applications. While density functional theory (DFT) calculations can provide valuable insight about these interactions, traditional DFT approaches with local exchangecorrelation functionals suffer from a poor description of non-bonding van der Waals (vdW) interactions. We examine here the contribution of vdW forces to the interaction of small organic molecules (methane, methanol, f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
54
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(56 citation statements)
references
References 73 publications
2
54
0
Order By: Relevance
“…Only the two uppermost Ni layers were fully relaxed, while the two bottom layers were fixed in the bulk positions; this procedure is often found to accelerate the convergence of calculated surface properties with respect to the thickness of the simulation slab. 34,35 The positions of the MAA molecule were also allowed to fully relax. In order to compensate for the use of an asymmetric slab, all simulations included a dipole correction as implemented in VASP, based on a method proposed by Makov and Payne.…”
Section: Computational Detailsmentioning
confidence: 99%
“…Only the two uppermost Ni layers were fully relaxed, while the two bottom layers were fixed in the bulk positions; this procedure is often found to accelerate the convergence of calculated surface properties with respect to the thickness of the simulation slab. 34,35 The positions of the MAA molecule were also allowed to fully relax. In order to compensate for the use of an asymmetric slab, all simulations included a dipole correction as implemented in VASP, based on a method proposed by Makov and Payne.…”
Section: Computational Detailsmentioning
confidence: 99%
“…However, the effect of van der Waals interactions can be positive or negative based on the results using current methods [38]. It has been demonstrated that the consideration of vdW interaction with some semi-empirical methods may overestimate the adsorption energies of organic species on surfaces of ionic crystals [39]. To solve this problem, a new Tkatchenko-Scheffler (TS) method based on the atoms-in-molecules (AIM) approach has been developed recently, which has been demonstrated to lead to accurate results for many molecular and solid systems [40].…”
Section: Dispersion Correctionsmentioning
confidence: 99%
“…This surface structure contains the double-bonded and neighbor bridging oxygen atoms and five-fold and six-fold coordinated titanium (Ti 5f , Ti 6f ) atoms with in-plane threefold coordinated O atoms as shown in figure 1. [5,11] The simulated surface in this work is set up at 3 x 2 x 4 supercell with a = 13.24 Å; b = 9.10 Å; c = 25.00 Å. The automatically generated Γcenter k-points grids are used for all of surfacerelated calculations after convergence testing.…”
Section: Computational Detailsmentioning
confidence: 99%
“…[3] Further, the rutile (1 1 0) face is the most stable surface of rutile phase and commonly studied in surface science. [3][4][5] In recent years, the elementary surface reactions on TiO 2 surfaces have increasingly been investigated but the origin and role of interactions have not been understood clearly. [2,10] Furthermore, this surface has become the prototype for single crystal investigations of photo-induced molecular reactions and adsorbate-surface interactions on TiO 2 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation